Pathogenicity of Curtobacterium flaccumfaciens pv. flaccumfaciens to several plant species - Silva Junior, Tadeu Antônio Fernandes da [UNESP]; Negrao, Djanira Rodrigues [UNESP]; Itako, Adriana Terumi [UNESP]; Maringoni, Antonio Carlos [UNESP] (Edizioni Ets, 2012)
Plants of different species were inoculated with a Curtobacterium flaccumfaciens pv. flaccumfaciens isolate by spray and stem puncturing. Common bean (Phaseolus vulgaris L.) plants inoculated with bacterial suspension in the aerial parts developed necrosis surrounded by a yellow halo at the edges of the leaflets, which progressed toward the center. Leaves of soybean plants inoculated by spraying developed symptoms of necrosis surrounded by a faint yellow halo at the edges. Necrotic lesions in the central portion of the lamina, surrounded by yellow halo, were also produced on this host. These lesions gave the leaves a rough (bumpy) aspect. The bacterium colonized endophytically the stems of wheat plants inoculated by wounding or spraying. Other plant species inoculated did not show necrosis of the shoots, wilting, or endophytic colonization of leaves and stems.
Keywords: Bean bacterial wilt; Phaseolus vulgaris; Soybean; Wheat